Illocutionary Analysis of Palestinians During Thufan Al-Aqsa : Pragmatics Study - Nida Husnia Ramadhani; Rinda Eka Mulyani; Muhammad Iberahim Mahmud (Indonesian Journal of Arabic Studies, 2025)
The protracted Palestinian–Israeli conflict has generated extensive global media attention, particularly following the Thufan Al-Aqsa incident in 2023. While numerous studies have examined the conflict from political, historical, and media perspectives, limited attention has been paid to Palestinian digital communication from a pragmatic and speech act theoretical framework. This study addresses this gap by analyzing the illocutionary intentions embedded in Palestinian social media discourse during Thufan Al-Aqsa. Grounded in speech act theory within pragmatics, this research employs a qualitative content analysis of selected video recordings disseminated via digital platforms. The data consist of Palestinian utterances systematically sampled and categorized according to illocutionary types, followed by contextual and functional analysis to uncover communicative intentions. The findings demonstrate that Palestinian digital discourse during Thufan Al-Aqsa prominently employs representative, directive, commissive, expressive, and declarative illocutions, reflecting functions of testimony, resistance, appeal, emotional expression, and identity assertion. These results highlight that social media functions not merely as an information channel but as a pragmatic space for political agency and meaning construction under conditions of conflict. The study contributes theoretically by extending speech act analysis to conflict-driven digital narratives, methodologically by integrating pragmatics with social media content analysis, and practically by offering insights into how marginalized communities articulate resistance and survival through digital communication.